2003
DOI: 10.1007/s00431-003-1321-9
|View full text |Cite
|
Sign up to set email alerts
|

How accurately can QT interval be measured in newborn infants?

Abstract: We determined inter-and intra-observer variability of measurements of QT and heart rate corrected QT (QTc) interval in newborn infants. In 55 newborns, a standard 12-lead electrocardiogram (ECG) with rhythm strip was analysed independently by three observers. QT and the preceding RR interval were measured in three different beats. The QTc interval was calculated using the Bazett formula (QTc = QT/ÖRR). Observers repeated their measurements after the recruitment period blinded for their first reading. Inter-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…In this study, four infants in the methadone group had a QTc≥500 ms. One of these infants had a heart rate of 88/min, but the infant was otherwise asymptomatic. The interobserver and intraobserver agreement reported in the study is acceptable for QTc intervals in infants and compares favourably with previous reported intraobserver variability for cardiologists 18. In this study, surprisingly, there was no correlation between maternal methadone dosage and prolongation of QTc.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, four infants in the methadone group had a QTc≥500 ms. One of these infants had a heart rate of 88/min, but the infant was otherwise asymptomatic. The interobserver and intraobserver agreement reported in the study is acceptable for QTc intervals in infants and compares favourably with previous reported intraobserver variability for cardiologists 18. In this study, surprisingly, there was no correlation between maternal methadone dosage and prolongation of QTc.…”
Section: Discussionsupporting
confidence: 86%
“…These investigations are widely practiced in the treatment of adults. The ECG, a determining factor in the diagnosis of hypoxic-ischemic cardiac insult in adults, is of less value in neonatal practice [11,12] . The small diameter of the chest in relation to the size of the electrodes and infant activity could make the examination useless.…”
Section: Discussionmentioning
confidence: 99%
“…One study of 53 ECG recordings from neonates showed large inter-observer and intra-observer differences. 15 Therefore, in our case, T-wave measurements were conducted in several beats, and the interpretation was confirmed by a paediatric cardiologist.…”
Section: Discussionmentioning
confidence: 79%